Using the Harvesting Method to Submit ETDs into ProQuest: A Case Study of a Lesser-Known Approach - Veve, Marielle (Information Technology and Libraries, 2020)
The following case study describes an academic library’s recent experience implementing the harvesting method to submit electronic theses and dissertations (ETDs) into the ProQuest Dissertations & Theses Global database (PQDT). In this lesser-known approach, ETDs are deposited first in the institutional repository (IR), where they get processed, to be later harvested for free by ProQuest through the IR’s Open Archives Initiative (OAI) feed. The method provides a series of advantages over some of the alternative methods, including students’ choice to opt-in or out from ProQuest, better control over the embargo restrictions, and more customization power without having to rely on overly complicated workflows. Institutions interested in adopting a simple, automated, post-IR method to submit ETDs into ProQuest, while keeping the local workflow, should benefit from this method.